2018
DOI: 10.14311/ap.2018.58.0069
|View full text |Cite
|
Sign up to set email alerts
|

H2 PERMEATION BEHAVIOR OF Cr2AlC AND Ti2AlC MAX PHASE COATED ZIRCALOY-4 BY NEUTRON RADIOGRAPHY

Abstract: Hydrogen uptake by nuclear fuel claddings during normal operation as well as loss of coolant during design basis and severe accidents beyond design basis has a high safety relevance because hydrogen degrade the mechanical properties of the zirconium alloys applied as cladding material. Currently, claddings with enhanced accident tolerance are under development. One group of such accident tolerant fuel (ATF) claddings are zirconium alloys with surface coatings reducing corrosion and high-temperature oxidation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…One route for corrosion protection is the development and application of temperature-resistant coatings with excellent barrier properties for hydrogen. Recently performed studies indicate that MAX phase materials might fulfill these requirements [2][3][4][5][6]. The general formula, M n+1 AX n , (short MAX) describes a family of materials consisting of an early transition metal (M), mostly a group 13 or 14 element (A) and nitrogen and/or carbon (X) with the stoichiometry of n = 1,2,3 [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One route for corrosion protection is the development and application of temperature-resistant coatings with excellent barrier properties for hydrogen. Recently performed studies indicate that MAX phase materials might fulfill these requirements [2][3][4][5][6]. The general formula, M n+1 AX n , (short MAX) describes a family of materials consisting of an early transition metal (M), mostly a group 13 or 14 element (A) and nitrogen and/or carbon (X) with the stoichiometry of n = 1,2,3 [7].…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study on the hydrogen barrier properties of MAX phase coatings was presented by C. Tang et al in [6]. Therein, ZrY-4 alloy cylinders were coated with Ti 2 AlC and Cr 2 AlC by a multilayer deposition followed by a subsequent annealing step.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that Cr2AlC films are amorphized at room temperature even at low doses; however, no amorphous phase was found up to 90 dpa at 623 K, indicating good radiation tolerance at elevated temperatures (Figure 11). Furthermore, both Ti2AlC and Cr2AlC coatings reduce hydrogen uptake effectively [161]. Wang et al also demonstrated good oxidation resistance of 10 µm-thick Cr2AlC coatings in air at 1100 °C [162].…”
Section: Max-phase Coatingsmentioning
confidence: 99%
“…[ 6,7 ] First neutron radiography investigations of the hydrogen permeability through coatings made of Ti 2 AlC and Cr 2 AlC MAX phases on Zircaloy‐4 showed that these coatings were robust diffusion barriers for the hydrogen, so MAX phases could be used as coatings of cladding materials for nuclear storages. [ 8 ] Theoretical investigations of the migration of interstitial H and O atoms in the Ti 2 AlN MAX phase proved that this coating could act as a protective diffusion barrier for oxygen and hydrogen. [ 9 ] The model of trapping the hydrogen by vacancies in the Ti 3 SiC 2 MAX phase was developed.…”
Section: Introductionmentioning
confidence: 99%